Learning microscopic organography using the didactic method of virtual computing in university students - Sotomayor Camayo, Justiniano (2014)
The aim of the study was to compare learning, of guided practices of Human Histology and Embryology subject in dental students from two peruvian universities using two techniques of microscopic organography teaching practices. Methodology: The study was quasi-experimental. There was a control group (50 students) on the traditional technique and an experimental group (50 students) where the virtual technique was used. In the control group a Zeiss electron microscope was used for observing laminas while in the experimental group a multimedia projector was used. Two evaluations were conducted (with 20 questions each) to measure learning about Stomatologic Embryology and Stomatologic Histology, a note for each unit was obtained and the mean for the overall learning of the subject. For comparison between groups the U Mann Whitney test was applied. Results and conclusions: The student learning about Stomatologic Embryology, Stomatologic Histology and the global had a median + interquartile range of 9+3.25, 11+4 and 10+2 points respectively in the control group and 11+2.25, 13+2 and 12+2 points respectively in the experimental group. Comparing learning of showed statistically significant differences (p <0.001). Global learning of the subject of Human Histology and Embryology was higher in students who received instruction using the virtual technique than those using the traditional technique.